Bimbingan Kelompok dengan Teknik Sosiodrama Sebagai Upaya Mengatasi Perilaku Bullying di Sekolah - Kurniawan, Drajat Edy; Pranowo, Taufik Agung (Jurnal Bimbingan dan Konseling Terapan, 2018)
Bullying behavior is a behavior that many found among people in recent times. Many argue that bullying behaviors include behaviors that aim to intimidate others, discredit others, and even injure others. Different forms of bullying behaviors, some of which include bullying, threatening, mocking, calling offensive calls, and isolating or alienating others in a group. There are many impacts of bullying behavior, including individuals who become inferior, depressed, depressed, or even self-rebellious and revengeful. Such impacts will be harmful to others as well as to the individuals concerned. Therefore it is necessary to attempt to overcome the bullying behavior. One way that can be used is through the application of group guidance with sociodrama technique. Sociodrama is one of group guidance techniques. Through sociodrama, individuals will be invited to play a role to train their ability to deal with bullying behavior in accordance with the drama theme being played.